2020
DOI: 10.1186/s12917-020-2268-z
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic antimicrobial resistance in Escherichia coli strains isolated from swine husbandries in North Western Germany – temporal patterns in samples from laboratory practice from 2006 to 2017

Abstract: Background: Since 2011, antibiotic usage has decreased continuously in livestock in Germany. Whether this is accompanied by a reduction in bacterial antimicrobial resistance has not been proven so far. In this study 3054 Escherichia coli (E. coli) isolates from pigs which had suffered from disease on 2161 farms in North Western Germany were evaluated retrospectively from 2006 to 2017 for trends in their antimicrobial resistance pattern. Data were substantially related to the "pre-reduction period" and were the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 43 publications
2
10
1
Order By: Relevance
“…The data was mostly collected in the North West, both for the different human populations and different food-producing animal populations. This is in line with the high density of livestock production in the North West ( 18 ) and high number of participating health care facilities in the human surveillance system ( 1 3 ) ( Supplementary Table 3 ). We studied only resistance to four antibiotics that were routinely included in all three monitoring and surveillance systems in one country.…”
Section: Discussionsupporting
confidence: 58%
“…The data was mostly collected in the North West, both for the different human populations and different food-producing animal populations. This is in line with the high density of livestock production in the North West ( 18 ) and high number of participating health care facilities in the human surveillance system ( 1 3 ) ( Supplementary Table 3 ). We studied only resistance to four antibiotics that were routinely included in all three monitoring and surveillance systems in one country.…”
Section: Discussionsupporting
confidence: 58%
“…Studies from Vietnam have reported lower MIC value of clinical isolates as 4 (µg/ml) [45] and MICs range of 4 to 16 μg/ml in E. coli isolates were reported from Chinese University Hospital [46]. The greater MIC value revealed these E. coli isolates as non-wild type [47]. The presence of multiple systems of resistance and multiple copy number of plasmids carrying mcr-1 gene may have played role in increasing the MIC value of colistin [48].…”
Section: Discussionmentioning
confidence: 97%
“…Finally, we excluded penicillin, clindamycin, and tilmicosin from the analysis as all isolates had the maximum MIC value. This could be due to natural resistance in E. coli to these substances as other studies have demonstrated 100% resistance to these drugs ( 44 , 45 ).…”
Section: Discussionmentioning
confidence: 93%